The Expert Right to Submit Petitions as an Exercise Form of Expert Initiative - O. G. Dyakonova (Теория и практика судебной экспертизы)
The issues of an expert right of initiative when undertaking a study is very relevant to this day since there is still no proper legal regulation. The provisions of legislation on expert activities of the member States of the Eurasian Economic Union, the Model Law of the Eurasian Economic Community on forensic activities, as well as scientific positions on the nature, structure, exercise, limits and regulation of expert initiative are analyzed in the article. An opportunity to establish the expert initiative right by entitling him to submit petitions connected with appointment and production of forensic examination is examined. The author proposes to make additions to the existing legislation on forensic activities to enshrine the specific expert right to submit a range of petitions. For instance, to invite other experts to examination; to extend the term of examination; to change the wording of the issues for expertise preserving their semantic content in the decision on the appointment of an examination, to withdraw permission for a proceedings participant to attend an examination if he obstructs the work of an expert. As a possible way to reduce the time and financial costs to resolute the expert’s petitions an exemplary order of their submission in electronic form is proposed.